Diachronic Semantic Shifts of Major Hebrew Theological Terms in Hosea: A Comparative Study of English and Indonesian Bible Translations - Joshua Octavianus; Agustinus Hary Setyawan (Universitas Nahdlatul Wathan Mataram, 2026)
This study examines diachronic semantic change in selected Hebrew theological terms in the Book of Hosea which are written in English and Indonesian Bible translations across different time periods. Though existing literature often examines semantic change within single linguistic traditions, comparative research across different cultural and linguistic contexts remains relatively underexplored. Therefore, the primary objective of this study is to investigate how theological meaning evolves when transposed into these distinct cultural and temporal contexts. Employing a qualitative descriptive design grounded in diachronic semantics and translation studies, the research analyzes five key lexemes of zĕnûnêyhā, ḥesed, ’āšûbā, bĕrît, and ruḥāmā that frequently appear in the Hebrew Masoretic Text and their renderings in the King James Version, New King James Version, Terjemahan Lama, and Terjemahan Baru Edisi 2. The results indicate that the English translation tradition exhibits relative semantic stability, while the Indonesian translations demonstrate systematic patterns as identified in 32 lexical examples, yielding 128 comparative data points. The findings suggest that the English translation tradition reveals relative lexical stability. In contrast, the Indonesian translations exhibit systematic patterns of semantic change, including narrowing, subjectivization, and amelioration. These patterns indicate that semantic change in biblical translation operates not only as a linguistic process but also serves as a form of theological and cultural adaptation. The results point to a diachronic shift in Indonesian translations from formal lexical representation toward the explicit encoding of internal theological states. Ultimately, this study contributes to the fields of diachronic semantics and translation studies by showing how cross-linguistic translation mediates theological meaning across historical and cultural contexts.